Chronic multiple mild stress induces sustained adverse psychological states in rats. Issue 15 (7th September 2022) - Yu, Tianze; Chen, Yi; Lu, Jiani; Gong, Luyun; Mao, Yuechen; Liu, Xinya; Zhou, Yiying; Guo, Lei; Wu, Xiang; Zhang, Junfang; Wang, Chuang; Shen, Haowei; et al.
Abstract : Adverse psychological states are stimulated by multiple types of environmental factors in human being. However, only few animal models of adverse psychological states were established by applying multiple types of stressors to mimic real conditions. A multisensory stress simulation device was designed to apply a combination of stressors to animals. Selected types and intensity of stressors were stimulated by this multisensory stress simulation device to induce chronic multiple mild stress (CMMS) in rats, modeling sustained adverse psychological states caused by long-term exposure in relative extreme environments with limited social interaction in human being. Fourteen-day treatment of CMMS-induced anhedonia, anxiety, and the loss of body weight in rats, which were similar to those in human being with adverse psychological states. Moreover, CMMS treatment leads to decreased production of serotonin and increased expression of corticotropin-releasing factor receptor 1, adrenocorticotropic hormone, and glucocorticoid in the brain, which were prevented by paroxetine and sertraline, two clinical-used antidepressants. Furthermore, these antidepressants prevented the CMMS-induced inhibition of brain-derived neurotrophic factor/cAMP-response element binding protein pathway, reduction of synaptic protein expression, and the activation of microglia and astrocytes in the hippocampus and the prefrontal cortex of rats. In addition, 14-day CMMS-induced long-term depressive-like behaviors, even after 14 days of CMMS treatment. And sertraline reversed CMMS-induced behavioral and biochemical changes in rats. All these results suggested that CMMS protocol induced sustained adverse psychological states in rats. By adjusting the intensity and the type of stressors in the multisensory stress simulation device, it might be practicable to establish animal models with complicated and changeable environmental factors.